Appropriateness of Helicobacter pylori eradication therapy in gastroenterology patients of a tertiary care hospital - Sreerag K. Vijayan, Emmanuel James, Ramakrishna P. Venugopal (Journal of Applied Pharmaceutical Science, 2019)
Recommended and widely used first-line treatment of Helicobacter pylori consists of a proton pump inhibitor, clarithromycin, and amoxicillin/metronidazole. Recent reports suggest an increase in resistance to these antibiotics, especially to clarithromycin which has adversely affected the effectiveness of this standard regimen, hence levofloxacin containing regimens have also been introduced. Our objective was to assess the appropriateness of clarithromycin and levofloxacin containing regimens for H. pylori eradication by considering the factors such as dose, duration of treatment, patient medication adherence, and H. pylori induced symptom relief. In this prospective observational study, 120 patients were enrolled on the basis of H. pylori induced symptoms, positive campylobacter-like organism (CLO) test, or histology proven H. pylori infection. Besides socio-demographic characteristics, endoscopic findings, CLO test results and H. pylori induced symptom eradication were documented. Majority of the patients (85.83%) received an eradication regimen consisting of clarithromycin + amoxicillin + pantoprazole and the remaining patients were prescribed levofloxacin containing regimens. H. pylori eradication regimen containing clarithromycin was more effective in symptom control. Based on both symptom relief and a negative CLO test on treatment completion, only 40% of the patients received benefit from the regimens. Moreover, overall therapy was unsatisfactory due to inappropriate dose, duration, or sub-optimal adherence.
Keywords: Amoxicillin, appropriateness of therapy, clarithromycin, gastroenterology patients, H. pylori eradication, levofloxacin, medication adherence, proton pump inhibitors.